2014
DOI: 10.1631/jzus.b1400029
|View full text |Cite
|
Sign up to set email alerts
|

Variation in copper and zinc tolerance and accumulation in 12 willow clones: implications for phytoextraction

Abstract: Willows (Salix spp.) have shown high potential for the phytoextraction of heavy metals. This study compares variations in copper (Cu) and zinc (Zn) tolerance and accumulation potential among 12 willow clones grown in a nutrient solution treated with 50 μmol/L of Cu or Zn, respectively. The results showed differences in the tolerance and accumulation of Cu and Zn with respect to different species/clones. The biomass variation among clones in response to Cu or Zn exposure ranged from the stimulation of growth to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…In spite of this, the efficiency of phytoextraction of all metals in Salix was particularly high in leaves. In many cases, the presented values were significantly higher than those recorded in other papers (Ahmed et al 2015) and the transport of metals inside plants was more effective in relation to Salix taxa other than the ones studied in this paper, when comparing, e.g., translocation factor values (Yang et al 2014).…”
Section: Discussioncontrasting
confidence: 68%
“…In spite of this, the efficiency of phytoextraction of all metals in Salix was particularly high in leaves. In many cases, the presented values were significantly higher than those recorded in other papers (Ahmed et al 2015) and the transport of metals inside plants was more effective in relation to Salix taxa other than the ones studied in this paper, when comparing, e.g., translocation factor values (Yang et al 2014).…”
Section: Discussioncontrasting
confidence: 68%
“…For example, no symptom of necrosis or chlorosis were observed in the leaves of P. glandulosa, suggesting that the dose of Cu +2 evaluated was not severely phytotoxic compared to P. juliflora. Similar results were observed in willow plants exposed to heavy metals, where the genetic variation was related with the tolerance capacity [18]. On the other hand, several studies show that the plants possess a sophisticated and interrelated and 72 to 96 h. Otherwise, the P. juliflora leaves exposed to cadmium did not show changes due to the exposure time and doses evaluated (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The interaction between Cd/Cu and other heavy metal elements has been investigated (Ernst et al 1992;Yang et al 2014). However, several reports on the interaction between Cd and Cu are complicated (Fig.…”
Section: Interactions Between CD and Cu In Phytoremediationmentioning
confidence: 99%
“…In contrast to common interactions between heavy metals, the interactions between Cd and Zn are mostly dependent on plant species (Bowen 1987, Lidon and Henriques 1993, Ernst et al 1992, McKenna et al 1993. Yang et al (2014) also reported that Cu and Zn are absorbed by willows via independent uptake mechanisms, which have been demonstrated in other plants by Ali et al (2004). The interaction between Cd and Cu has not been explicitly reported.…”
Section: Introductionmentioning
confidence: 96%